AATF inhibition exerts antiangiogenic effects against human hepatocellular carcinoma - Suresh, Diwakar; Srinivas, Akshatha N.; Prashant, Akila; Satish, Suchitha; Vishwanath, Prashant; Nataraj, Suma M.; Koduru, Srinivas V.; Santhekadur, Prasanna K.; Kumar, Divya P. (Frontiers in Oncology, 2023)
Background and Aims: Angiogenesis is a key factor in the growth and metastasis of hepatic tumors and thus a potential therapeutic target in hepatocellular carcinoma (HCC). In this study, we aim to identify the key role of apoptosis antagonizing transcription factor (AATF) in tumor angiogenesis and its underlying mechanisms in HCC. Methods: HCC tissues were analyzed for AATF expression by qRT-PCR and immunohistochemistry. Stable clones of control and AATF knockdown (KD) were established in human HCC cells. The effect of AATF inhibition on the angiogenic processes was determined by proliferation, invasion, migration, chick chorioallantoic membrane (CAM) assay, zymography, and immunoblotting techniques. Results: We identified high levels of AATF in human HCC tissues compared to adjacent normal liver tissues, and the expression was found to be correlated with the stages and tumor grades of HCC. Inhibiting AATF in QGY-7703 cells resulted in higher levels of pigment epithelium-derived factor (PEDF) than controls due to decreased matric metalloproteinase activity. Conditioned media from AATF KD cells inhibited the proliferation, migration, and invasion of human umbilical vein endothelial cells as well as the vascularization of the chick chorioallantoic membrane. Furthermore, the VEGF-mediated downstream signaling pathway responsible for endothelial cell survival and vascular permeability, cell proliferation, and migration favoring angiogenesis was suppressed by AATF inhibition. Notably, PEDF inhibition effectively reversed the anti-angiogenic effect of AATF KD. Conclusions: Our study reports the first evidence that the therapeutic strategy based on the inhibition of AATF to disrupt tumor angiogenesis may serve as a promising approach for HCC treatment.